Dynamic Capital Structure and Its Speed of Adjustment: a Case of Listed Manufacturing Firms in Indonesia - Anisti, Novia Putri; Chalid, Dony Abdul (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
This study examines the determining factors and the speed of adjustment of manufacturing firms’ capital structure in Indonesia. This research uses data of 118 listed manufacturing companies from 2014 to 2018 and offers a continuation of Indonesia’s existing literature by applying a dynamic model. The results reveal that Indonesian manufacturing firms practice optimal capital structure and are altered by firm-specific and time-varying factors. Firms’ decisions regarding capital structure are determined by firm-specific factors: non-debt tax shields, tangibility, and stock price performance. The results also indicate the speed of adjustment does exist, although the speed of adjustment finds lower than in previous research. The slowdown of the manufacturing industry growth from 2014 to 2018 turns out to be in line with the slow pace of leverage adjustment.